Colonialism and Sisterhood: Japanese Female Activists and the "Comfort Women" Issue. (January 2021) - Park, Sara
This article clarifies how wartime/colonial responsibility and sisterhood are mediated in the accounts of Japanese female activists who support so-called "comfort women" or the Japanese military sexual slavery issue, by using interviews of Japanese female activists, this article tries to answer this question. The Japanese female activists experience the changes in the their identities from collective "women" and/or "Japanese" while they continue participating in the movement. The interviewees always emphasize their feeling of responsibility as Japanese, former colonizer and perpetrator as well as Japanese citizen who have not yet settled this issue. At the same time, they sympathize with the survivors as fellow women; therefore, they call for a formal apology and governmental compensation. Nationalism and gender coexist in different dimensions; thus, being a member of a Japanese nation with wartime/colonial responsibility does not contradict the sympathy and compassion with the victims of Japanese military sexual slavery.